The Concept Of Amnesty Act And Its Difference From Pardon - Dumaev Fayzullokhon Suvankhanovich (Global Scientific Publishing, 2023)
Amnesty Act is to provide an opportunity for a certain category of persons who have committed a crime to recover morally without the use of criminal justice measures, or to alleviate the condition of persons for whom such measures have been applied. The goal envisaged from the adoption of the amnesty act is, above all, the implementation of the expression of the principle of humanism in the state and society. Misapplication of amnesty can cause severe consequences for the individual and society. The insufficient legal regulation of this institution presents various difficulties in the practical application of the Amnesty Act. The article contains opinions on the concept of the amnesty act, its aspects different from pardons.
Keywords: concept of аmnesty аct; pardon; crime; institution